Career interventions and techniques : a complete guide for human service professionals - Duggan, Molly H.; Jurgens, Jill C. (Boston : Pearson/Allyn and Bacon, 2007)
This unique text provides detailed information on career development interventions appropriate to use with some of the most common populations with whom entry-level human service professionals often work.
Includes bibliographical references and indexes.
Keywords: Career development -- Handbooks, manuals, etc. -- United States United States; People with social disabilities -- Handbooks, manuals, etc. -- Services for -- United States; Human services personnel -- Handbooks, manuals, etc. -- United States; Social workers -- Handbooks, manuals, etc. -- United States; Counselors